2009
DOI: 10.1007/s11664-009-0991-0
|View full text |Cite
|
Sign up to set email alerts
|

Progress Report on BSST-Led US Department of Energy Automotive Waste Heat Recovery Program

Abstract: As global consumption of energy continues to increase at an exponential rate, the need to find technologies that can help reduce this rate of consumption, particularly in passenger vehicles, is imperative. This paper provides a progress report on the BSST-led US Department of Energy-sponsored automotive thermoelectric waste heat recovery project, which has transitioned from phase 3 and is completing phase 4. Thermoelectric generator (TEG) development will be discussed, including modeling and thermal cycling of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
41
0
2

Year Published

2011
2011
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 110 publications
(48 citation statements)
references
References 2 publications
(3 reference statements)
0
41
0
2
Order By: Relevance
“…[2] Ideal thermoelectric materials should possess a high dimensionless figure of merit, ZT, defined as ZT = S 2 T/ ρ(κ e + κ L ), where S is the Seebeck coefficient, T is the absolute temperature, ρ is the electronic resistivity, and κ e and κ L are the carrier and lattice thermal conductivity, respectively. [1,3] Majority of IV-VI compounds tend to be dominant thermoelectric materials in the medium-temperature (500-900 K) range; these include most of lead chalcogenides (PbTe, [4][5][6][7][8] PbSe, [9,10] and PbS [11,12]), and tin chalcogenides (SnTe, [13,14] SnSe, [15][16][17] and SnS [18]).…”
Section: Introductionmentioning
confidence: 99%
“…[2] Ideal thermoelectric materials should possess a high dimensionless figure of merit, ZT, defined as ZT = S 2 T/ ρ(κ e + κ L ), where S is the Seebeck coefficient, T is the absolute temperature, ρ is the electronic resistivity, and κ e and κ L are the carrier and lattice thermal conductivity, respectively. [1,3] Majority of IV-VI compounds tend to be dominant thermoelectric materials in the medium-temperature (500-900 K) range; these include most of lead chalcogenides (PbTe, [4][5][6][7][8] PbSe, [9,10] and PbS [11,12]), and tin chalcogenides (SnTe, [13,14] SnSe, [15][16][17] and SnS [18]).…”
Section: Introductionmentioning
confidence: 99%
“…Similarly, inefficiencies in a turbine engine for an Abrams tank means that exhaust gasses can contain megawatts of thermal energy. Thus, the auto industry (5), Department of Energy (6)(7)(8), TARDEC (9), and others have all investigated waste-heat recovery as a way to improve overall system efficiency. Depending on the vehicle type and driving conditions, fuel mileage improvements on the order of 5% during highway cruising are expected (8, 10) Army vehicle modernization programs, which desire more onboard electrical generation, could potentially meet their targets by capturing and converting waste-heat energy to avoid increased fuel usage.…”
Section: Heat To Electricity -Army Applicationsmentioning
confidence: 99%
“…Engineers there have looked toward advancing heat exchanger and fan design to impact the SWaP of cooling system radiators and vapor compression cycle (VCC) condensers and evaporators (9). For a VCC, an improved condenser could reduce compressor SWaP requirements.…”
Section: Heat Transfer -Army Applicationsmentioning
confidence: 99%
“…With the present thermoelectric materials having figures of merit ZT≈1.5, the conversion efficiencies 5-10% in power generation can be achieved. However, an increase in efficiency for direct heat-to-electricity are sought through the methods of nanostructuring and fabrication [2,3], novel bulk designs such as cascading [4], multistage [5] and segmented [6][7][8] TEDs and use of new materials [1].…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, for T h = 973 K and T c = 300 K, El-Genk et al [7] showed a peak conversion efficiencies of 16.69% and 7.4% for skutterudite and SiGe segmented thermoelectric generators, respectively. Crane and Lagrandeur [8] also recently investigated the segmented TEDs in automotive waste heat recovery systems and achieved a power output of 125W operating at inlet exhaust gas temperature of 650ºC.…”
Section: Introductionmentioning
confidence: 99%